Prediksi Jumlah Mahasiswa Registrasi Per Semester Menggunakan Linier Regresi Pada Universitas Ichsan Gorontalo - Bengnga, Amiruddin; Ishak, Rezqiwati (ILKOM Jurnal Ilmiah, 2018)
Improving the quality of education, service quality and accreditation value increase is the hope of all universities, especially at Ichsan University of Gorontalo. One of the factors to achieve this is the increasing number of students who make the payment registration every semester. Based on the report in PDPT Dikti reporting year 2017/2018 has the number of students ± 9,000 people, from the analysis of the last 4 years the number of unregistered students tends to increase and students registerasi tends to decrease, if this is not considered, it will have an impact on the achievement of the above expectations. To overcome these problems, need to be done prediction technique using Linear Regression and MAPE method. The purpose of this research is to build an application to predict the number of registration students. Based on the results of research from 2 selected study program of Informatics Engineering, the result of error rate is 4.24% or the accuracy level is 95.76%, and for the Law Study program, the error rate is 7.69% or the accuracy level is 92.31%, thus the application already built is feasible to use.